Representation Construction Approach: A Guided Inquiry Pedagogy for Science - Hubber, Peter (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This paper describes the development and implementation of a guided-inquiry approach to teachingscience which reflects the increasing attention given to the role of representation in learning science aswell as knowledge creation in science. This representation construction approach (RCA) involveschallenging students to generate and negotiate the representations (text, graphs, models, diagrams) thatconstitute the discursive practices of science, rather than focusing on the text-based, definitional versionsof concepts. In working with teachers in the development and refinement of the approach a design-basedresearch methodology was employed. The investigation of the approach, and teachersâ experienceinvolved video capture and analysis, and teacher interviews whilst documentation and analysis of studentlearning occurred through analysis of class discussion through whole class and small group videocapture, collection of student artefacts, pre- and post-tests, and student stimulated recall interviews. Theapproach has been successful in demonstrating enhanced outcomes for students, in terms of sustainedengagement with ideas, and quality learning, and for teachers enhanced pedagogical knowledge andunderstanding of how knowledge in science is developed and communicated.